Egg-box model-based gelation of alginate and pectin: A review - Cao, Lianqi; Lu, Wei; Mata, Analucia; Nishinari, Katsuyoshi; Fang, Yapeng (Carbohydrate polymers, 2020)
[Display omitted] •Chemical structure affected the gelation of alginate and pectin in a different way•pH, temperature and co-solute can significantly influence the gelation process•Pectin showed a different gelation mechanism from alginate•Oligosaccharides potentially can control the gelation of alginate and pectin Alginate and pectin are emblematic natural polyuronates that have been widely used in food, cosmetics and medicine. Ca-dependent gelation is one of their most important functional properties. The gelation mechanisms of alginate and pectin, known as egg-box model, were believed to be basically the same, because their Ca-binding sites show a mirror symmetric conformation. However, studies have found that the formation and the structure of egg-box dimmers between alginate and pectin were different. Very few studies have reviewed those differences. Therefore, this study was proposed to first summarize the intrinsic and extrinsic factors that can influence the gelation of alginate and pectin. The differences in the effect of these factors on the gelation of alginate and pectin were then discussed. Meanwhile, the similarity and difference in their gelation mechanism was also summarized. The knowledge gained in this review would provide useful information for the practical applications of alginate and pectin.